2023
DOI: 10.1002/cre2.761
|View full text |Cite
|
Sign up to set email alerts
|

Resin cement selection for different types of fixed partial coverage restorations: A narrative systematic review

Safoura Ghodsi,
Mina Shekarian,
Mohammad Mostafa Aghamohseni
et al.

Abstract: ObjectiveThe aim of this study was to review the selection criteria of resin cements for different types of partial coverage restorations (PCRs) and investigate if the type of restorations or restorative materials affect the type of selected resin cement.Materials and MethodsAn electronic search (1991–2023) was performed in PubMed, Medline, Scopus, and Google Scholar databases by combinations of related keywords.ResultsA total of 68 articles were included to review the selection criteria based on the advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Self‐adhesive cement has been recommended for the cementation of ceramic inlays and onlays. Clinical studies have shown that conditioning of dentin (Ghodsi et al, 2023 ) and etching of outer enamel (Peumans et al, 2013 ) are unnecessary for restorations with mechanical interlocking. This type of cement offers cost‐efficiency and simplified application, eliminating the need for complex protocols that can increase the risk of contamination and material application issues (Ghodsi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self‐adhesive cement has been recommended for the cementation of ceramic inlays and onlays. Clinical studies have shown that conditioning of dentin (Ghodsi et al, 2023 ) and etching of outer enamel (Peumans et al, 2013 ) are unnecessary for restorations with mechanical interlocking. This type of cement offers cost‐efficiency and simplified application, eliminating the need for complex protocols that can increase the risk of contamination and material application issues (Ghodsi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…simplified application, eliminating the need for complex protocols that can increase the risk of contamination and material application issues (Ghodsi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion aims to form a clinically durable link between resin cement and tooth tissues as well as between resin cement and ceramic restoration [12]. Various types of resin cements are available and are generally categorized based on the application protocols: total etch and rinse systems (conventional), self-etch systems, and self-adhesive systems (all-in-one cement systems) [13].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the steps of cementation and simplify the clinical procedures, self-adhesive resin cements are preferred. Besides simplicity, moisture tolerance, dimensional stability, and a rapid setting time, self-adhesive cements rarely display postoperative sensitivity and usually provide good esthetics [13]. They also have the potential for mechanical and chemical bonding and function by strengthening the ceramic as well as the tooth surface especially with veneer restorations [12,14].…”
Section: Introductionmentioning
confidence: 99%